THE CHARACTERISTICS AND MODERN PROBLEMS OF ISLAMIC BANKS - A. A. Al-Azzawi (Publishing House of the State University of Management, 2016)
The article examines the difference between the principles of operation of Islamic banks from the traditional commercial banks, list the existing problems that must be overcome for integration of Islamic banking in traditional financial industry.